Assessing Lettuce Exposure to a Multipharmaceutical Mixture under Hydroponic Conditions: Findings through LC-ESI-TQ Analysis and Ecotoxicological Assessments - Mravcová, Ludmila; Jašek, Vojtěch; Hamplová, Marie; Navrkalová, Jitka; Amrichová, Anna; Zlámalová Gargošová, Helena; Fučík, Jan (ACS omega, 2024)
The escalating global water scarcity demands innovative solutions, one of which is hydroponic vegetable cultivation systems that increasingly use reclaimed wastewater. Nevertheless, even treated wastewater may still harbor various emerging organic contaminants, including pharmaceuticals. This study aimed to comprehensively assess the impact of pharmaceuticals, focusing on bioconcentration factors (BCFs), translocation factors (TFs), pharmaceutical persistence in aqueous environment, ecotoxicological end points, and associated environmental and health risks. Lettuce (Lactuca sativa) was cultivated hydroponically throughout its entire growth cycle, exposed to seven distinct concentration levels of contaminants ranging from 0 to 500 μg·L-1 over a 35-day period. The findings revealed a diverse range of BCFs (2.3 to 880 L·kg-1) and TFs (0.019-1.48), suggesting a high potential of pharmaceutical uptake and translocation by L. sativa. The degradation of 20 pharmaceuticals within the water-lettuce system followed first-order degradation kinetics. Substantial ecotoxicological effects on L. sativa were observed, including increased mortality, alterations in root morphology and length, and changes in biomass weight (p < 0.05). Furthermore, the estimated daily intake of pharmaceuticals through L. sativa consumption suggested considerable health risks, even if lettuce would be one of the many vegetables consumed. It is hypothetical, as the values were calculated. Moreover, this study assessed the environmental risk associated with the emergence of antimicrobial resistance (AMR) in aquatic environments, revealing a significantly high risk of AMR emergence. In conclusion, these findings emphasize the multifaceted challenges posed by pharmaceutical contamination in aquatic environments and the necessity of proactive measures to mitigate associated risks to both environmental and human health.